Employing the aesthetics of Coptic art and its symbols in contemporary mural treatments - an applied study - Nehal Ramadan sayed; Ahmed Shehata Abul-Mag; Nermin Saeed Abbas (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
Mural painting is a communication method from the oldest individual and collective creations known for thousands of years, it has a great role expressing peoples’ culture and identifying social customs and traditions, also it has been linked to historical religious events of civilizations. Every civilization has a special character, style and symbols which consistent of the intellectual concepts that distinguish it . Heritage is the inheritance of peoples from their grandparents, as we inherited customs, traditions, arts and literature in all its forms from our predecessors. Therefore, its entire art expressed the environment, social life, daily practices and other various human feelings. man witnessed great developments recently until it corresponded to the modern era, within the framework of human control over nature and its adaptation to technology using materials that fit with urban surfaces, processing its designs aesthetically and functionally as it emphasizes the link between the place and the human being, to form a designed and outlined visual image through a studied scientific approach through theoretical and field studies. Each place needs a dedicated study to know the design that fits the spirit of it, taken from the styles And civilized landmarks, Coptic art was chosen, used and inspired by it in an environmental coordination and inventing contemporary aesthetic mural designs with the characteristics and spirit of the Egyptian identity and also linked to a historical aesthetic link stemming from the concepts of civilization and heritage in the place and have a positive role reflected on the human .